Problems with Aging Vessels in High Temperature Plant. (2015) - Furtado, H.C.; Felippe, L.; da Silveira, T.L.; Pascual, R.; Le May, I.
Abstract: The paper describes measures taken to reinforce the safe operation of aging power plant, rather than replacing it at the end of its normal life. Of particular concern in steam plant are superheaters and deaerators, both having potentially severe consequences as a result of failure. As a result of measures taken continued safe operation was possible.